Exploring factors influencing Black South African Millennials when considering African Ankara fashion - Mbumbwa, Tendai (Marketing, 2017)
The cyclical evolution of fashion has been based on the designs and styles composed in the fashion capitals of the world. Novelty and expression have been determinants of leading fashion. African fashion portrays both these elements through the vibrant fabric and culturally inspired pieces of clothing. With Western fashion dominating South African shopping centres, whether the younger and significant black South African Millennial (BSAM) cohort members ascribe any value to African fabric fashion is a matter of interest. The objective of this study is to explore, investigate and ascertain what factors BSAMs consider to be influential in their consideration of AFF. The adoption of fashion is a behaviour, which is preceded by a consumer holding the intention to so act; the intention to adopt fashion is influenced and altered by multiple different factors; AFF is arguably "new" fashion to the target population, based on the dominance of first-world fashion in the country; thus it is of interest to see what factors BSAMs consider to be influential when considering AFF. The data for this interpretivist study was collected through the use of a qualitative research methodology. The data were analysed manually. The theoretical framework and the literature review showed that the Theory of Planned Behaviour (TPB) was the basic theory for the study. This model was modified in line with the objectives of this study. Five factors structure the model, namely: attitude, social values (normative variables), fashion involvement, country-of-origin (COO) effect and consumer ethnocentrism (CE) (all perceived control variables). The generation, which is entering the working world and whose fashion selection is increasingly coming under their own control, desire to buy the fashion at affordable prices. Companies that target the cohort should recognise the pride, which the cohort holds in being African. Their pride must be recognised and acknowledged, and even supported; in order to appeal to this generation. Musical celebrities should be used in marketing campaigns; and the social media should be a channel utilised; since much interest in the medium has been shown by the findings of this study.